2007
DOI: 10.1111/j.1365-2133.2007.08238.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive supravenous granulomatous nodular eruption in a human immunodeficiency virus-positive intravenous drug user treated with highly active antiretroviral therapy

Abstract: We describe a 41-year-old human immunodeficiency virus-infected woman with a previous history of intravenous drug abuse, who developed multiple linear nodules following the superficial veins on both arms. Histopathological examination disclosed a dermal histiocytic inflammatory reaction with sarcoid-like granuloma formation occasionally showing an intracytoplasmic refractile material in the histiocytic cells. Nodular lesions developed progressively after starting on highly active antiretroviral therapy (HAART)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In that case, the antigen implicated was a foreign body in relationship with previous addiction to intravenous drugs. 2 Histopathologic differential diagnosis of our case includes the so-called nodular granulomatous phlebitis. 10 This entity is now considered a fourth type of tuberculid, because the lesions develop in patients with hypersensivity to purified protein derivate, but without active tuberculosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In that case, the antigen implicated was a foreign body in relationship with previous addiction to intravenous drugs. 2 Histopathologic differential diagnosis of our case includes the so-called nodular granulomatous phlebitis. 10 This entity is now considered a fourth type of tuberculid, because the lesions develop in patients with hypersensivity to purified protein derivate, but without active tuberculosis.…”
Section: Discussionmentioning
confidence: 97%
“…In our literature review, we have only found one previously described case of panniculitis as clinical manifestation of IRIS, but in that patient the panniculitic process was interpreted as the result of worsening of an infectious disease or as a foreign body granuloma reaction. 2 We report the first case of superficial thrombophlebitis as a clinical manifestation of IRIS.…”
Section: Introductionmentioning
confidence: 97%
“…25,26 The granulomatous component may be noninfective in origin, encompassing foreign body granulomas, granuloma annulare, and an immune host response to tumor cells, tumor substances, or to chemotherapeutic agents. [27][28][29][30] Such immune granulomas are sarcoidal in type, commonly associated with carcinomas, and lymphomas. 27 Described extremely rarely in sarcomas, 27 sarcoidal granulomas have been described once, to date, in classic KS.…”
Section: Discussionmentioning
confidence: 99%
“…One of them consisted of multiple, linear nodular lesions that develop at cutaneous intravenous drug injection sites and that may mimic polyarteritis nodosa, false aneurysms, and lymphatic spread of infections. 77 Histopathologically, these lesions show a sarcoidal granulomatous reaction to extravasated suspended drug particles in which inert material has been identified. 77 An IRISassociated foreign body granulomatous reaction has also been described in tattoos and in tribal scars containing long-standing burnt carbon.…”
Section: Systemic Drugsmentioning
confidence: 99%
“…77 Histopathologically, these lesions show a sarcoidal granulomatous reaction to extravasated suspended drug particles in which inert material has been identified. 77 An IRISassociated foreign body granulomatous reaction has also been described in tattoos and in tribal scars containing long-standing burnt carbon. 78 It has been hypothesized that a highly active antiretroviral therapy-augmented T-helper response with macrophage activation via interleukin 2 and interferon delta is responsible for these granulomatous reactions as an expression of IRIS.…”
Section: Systemic Drugsmentioning
confidence: 99%